2016
DOI: 10.1267/ahc.16031
|View full text |Cite
|
Sign up to set email alerts
|

Induced Expression of Cancer Stem Cell Markers ALDH1A3 and Sox-2 in Hierarchical Reconstitution of Apoptosis-resistant Human Breast Cancer Cells

Abstract: We established an experimental system that can induce p53-dependent apoptosis by doxycycline treatment to analyze characteristics of the apoptosis-resistant cancer cell subpopulation in the human breast cancer cell line HCC1937. Expression patterns of the stem cell markers, ALDH1A3 and Sox-2, the luminal differentiation marker, GATA3 and the proliferation index marker, Ki-67 were analyzed using immunostaining and fluorescence-activated cell sorting (FACS). After doxycycline treatment, the number of viable cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…Annexin V-staining suggests that ALDH hi cells may be more apoptosis-resistant than ALDH lo ones. Higher apoptosis-resistance of ALDH hi vs. ALDH lo cells has been reported in various cancer stem cells ( 43 45 ). Silencing ALDH1A by siRNA or shRNA in human melanoma cancer stem cells led to cell cycle arrest, apoptosis and decreased cell viability in vitro and reduced tumorigenesis in vivo ( 45 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Annexin V-staining suggests that ALDH hi cells may be more apoptosis-resistant than ALDH lo ones. Higher apoptosis-resistance of ALDH hi vs. ALDH lo cells has been reported in various cancer stem cells ( 43 45 ). Silencing ALDH1A by siRNA or shRNA in human melanoma cancer stem cells led to cell cycle arrest, apoptosis and decreased cell viability in vitro and reduced tumorigenesis in vivo ( 45 ).…”
Section: Discussionmentioning
confidence: 85%
“…Several studies showed that ALDH1A3 is a cancer stem cell gene. ALDH1A3 expression was detected in 78% of small-sized Ki-67 + proliferating progenitor cells in the human breast cancer cell line HCC1937 ( 43 ). Most recently, ALDH1A3 was shown to affect colon cancer in vitro proliferation and invasion depending on CXCR4 status ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…ALDH1A3, one of the subtypes of the ALDH family, was proposed as a novel clinical CSC marker showing a clear correlation between CSC prevalence and the development of metastatic breast cancer [8, 38]. ALDH1A3 was found to be expressed in not only CSCs but also highly proliferating progenitor cells in TNBC [20]. Sox-2 (Sex-determining region Y (SRY)-box binding protein-2) plays an important role in the maintenance of the pluripotent stem cell state and regulation of embryonic development [2, 4, 44, 57, 58], and is associated with breast CSCs [26].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is one of the pathways of cell death; however, cancer cells survival is promoted by the induction of an apoptosis resistance mechanism ( 59 ). A previous study reported that aldehyde dehydrogenase family 1 member A3 (ALDH1A3) and sex determining region Y box 2 (Sox-2) regulated the mechanism of apoptosis resistance in BC cells ( 60 ); however, GPS-mediated regulation of ALDH1A3 and Sox-2 has not been reported. TNF-α is a mediator of inflammation and is a member of a family of >20 related proteins including lymphotoxin-a, CD30 ligand, CD40 ligand, Fas ligand and TRAIL ( 61 ).…”
Section: Discussionmentioning
confidence: 99%